Emergence of bullous pemphigoid under treatment of mycosis fungoides with mogamulizumab - Lukas D. Uleer; Carmen Loquai; Iakov Shimanovich; Cyrus Khandanpour; Jasper N. Pruessmann; Patrick Terheyden; Christian D. Sadik (JEADV Clinical Practice)
Abstract Mycosis fungoides (MF) is the most common cutaneous T cell lymphoma. Since 2018, mogamulizumab, an antibody directed to to the chemokine receptor CCR4, is licensed for the treatment of MF. Treatment with mogamulizumab is associated with the precipiation of different types of skin rashes summarized as mogamulizumab‐associated rash. Here, we report the emergence of severe bullous pemphigoid (BP) in a patient suffering from severe MF and treated with mogamulizumab. BP is an autoimmune blistering skin disease causing severe pruritus and subepidermal blisters and, consequently, erosions. It is driven by autoantibodies against BP180, a protein of the dermal‐epidermal adhesion complex. The parallel occurrence of MF and BP led to a bizarre clinical and histopathological presentation blending features of MF and BP. Among others, the patient developed multiple large erosions with a diameter of up to 15 cm, and histopathology featured subepidermal clefts with a mixed dermal infiltrate and atypical lymphocytes forming a superficial dermal lichenoid infiltrate and showing epidermotropism, including above the subepidermal clefts. Immunopathology revealing linear depositions of IgG and C3 at the dermal‐epidermal junction and very high serum levels of anti‐BP180‐NC16A IgG were instrumental to diagnose BP and to distinguish it from mycosis fungoides bullosa, an extremely rare variant of MF. This case illustrates that immunopathology for BP should be conducted in patients with MF developing pruritus and blisters, although both can also be a symptom of MF. Our case alone does not allow determining whether the emergence of BP under mogamulizumab treatment was a mere coincidence or was in a causal relationship. The latter scenario would at BP to the possible clinical presentations of mogamulizumab‐associated rashes.